Compounding effects of white pine blister rust, mountain pine beetle, and fire threaten four white pine species. Issue 10 (12th October 2020) - Dudney, Joan C.; Nesmith, Jonathan C. B.; Cahill, Matthew C.; Cribbs, Jennifer E.; Duriscoe, Dan M.; Das, Adrian J.; Stephenson, Nathan L.; Battles, John J.
Abstract: Invasive pathogens and bark beetles have caused precipitous declines of various tree species around the globe. Here, we characterized long‐term patterns of mountain pine beetle ( Dendroctonus ponderosae ; MPB) attacks and white pine blister rust, an infectious tree disease caused by the pathogen, Cronartium ribicola . We focused on four dominant white pine host species in Sequoia and Kings Canyon National Parks (SEKI), including sugar pine ( Pinus lambertiana ), western white pine ( P. monticola ), whitebark pine ( P. albicaulis ), and foxtail pine ( P. balfouriana ). Between 2013 and 2017, we resurveyed 152 long‐term monitoring plots that were first surveyed and established between 1995 and 1999. Overall extent (plots with at least one infected tree) of white pine blister rust (blister rust) increased from 20% to 33%. However, the infection rate across all species decreased from 5.3% to 4.2%. Blister rust dynamics varied greatly by species, as infection rate decreased from 19.1% to 6.4% in sugar pine, but increased in western white pine from 3.0% to 8.7%. For the first time, blister rust was recorded in whitebark pine, but not foxtail pine plots. MPB attacks were highest in sugar pines and decreased in the higher elevation white pine species, whitebark and foxtail pine. Both blister rust and MPB were important factors associated with elevated mortality in sugar pines. We did not, however, find a relationship between previous fires and blister rust occurrence. In addition, multiple mortality agents, including blister rust, fire, and MPB, contributed to major declines in sugar pine and western white pine; recruitment rates were much lower than mortality rates for both species. Our results highlighted that sugar pine has been declining much faster in SEKI than previously documented. If blister rust and MPB trends persist, western white pine may follow similar patterns of decline in the future. Given current spread patterns, blister rust will likely continue to increase in higher elevations, threatening subalpine white pines in the southern Sierra Nevada. More frequent long‐term monitoring efforts could inform ongoing restoration and policy focused on threats to these highly valuable and diverse white pines.